RELIGION-BASED COGNITIVE BEHAVIOR THERAPY WITH SELF MANAGEMENT TECHNIQUES TO IMPROVE STUDENTS' LEARNING MOTIVATION - Siti Hafshah Masduqie; Endang Pudjiastuti Sartinah; Budi Purwoko (AT-TAJDID, 2022)
This paper focused on the application of one psychological approach, it is Islamic cognitive behavior therapy (CBT) on students of Madrasah Aliyah As-Syafi'e Kapubaten Pamekasan who are less enthusiastic in learning because of low learning motivation. This research is important because low motivation or interested in learning has become a serious threat to the future of many students as the nation's next generation. The purpose of implementing Islamic-based CBT is to raise students' awareness of the importance of learning and to get rid of or neutralize everything that is negative that can lead to lazy learning attitudes. In the process, cognitive behavior therapy is also combined with self-management techniques. This technique provides guidance for the therapist to initiate treatment actions for students with problems. The method used in this article is a descriptive qualitative method with a literature review.Keywords: Cognitive Behavior, Beligion-Based Therapy, Students Learning Motivation